Knowledge of managers on the National Mental Health Policy - Rafaella Leite Fernandes; Francisco Arnoldo Nunes de Miranda; Kalyane Kelly Duarte de Oliveira; Clara Tavares Rangel; Danyella Augusto Rosendo da Silva Costa; Izabella Bezerra de Lima Moura
ABSTRACT Objective: Identify the knowledge of mental health service managers about the national mental health policy. Method: This is a qualitative study conducted with 20 coordinators, who were submitted to a structured interview. Data were categorized in a thematic analysis using ALCESTE software. Results: The results produced the following categories: Back to society: protagonism and autonomy of patients; Interprofessional team: assignments and activities; Structuring of a psychosocial care network; Challenges affecting the service; Distance between policy and practice. Final Considerations: Public managers demonstrated they are aware of the key concepts for effective structuring of a psychosocial care network based on patient protagonism and autonomy, the assignments and activities performed by interprofessional teams, and the challenges found while structuring a psychosocial care network.